Integrative taxonomic analyses reveal first country records of Occidozyga shiwandashanensis Chen, Peng, Liu, Huang, Liao & Mo, 2022 and Hylarana latouchii (Boulenger, 1899) (Anura, Dicroglossidae, Ranidae) from Vietnam - Tung Tran; Chung Hoang; Anh Luong; Truong Nguyen; Thomas Ziegler; Cuong Pham (Biodiversity Data Journal, 2023)
Occidozyga shiwandashaensis was recently discovered from Guangxi Province of China. Hylarana latouchii is a widespread species in southern China, including Hong Kong and Taiwan. Both species are expected to be found in the border areas between Vietnam and China; however, no records of these frogs have been documented from Vietnam so far.We record two species of amphibians for the first time from Vietnam, namely Occidozyga shiwandashaensis from Bac Giang Province and Hylarana latouchii from Hai Phong City and Quang Ninh Province in northern Vietnam. Morphologically, the Vietnamese representatives of O. shiwandashanensis resemble the type series from China. The specimens of H. latouchii from Vietnam slightly differ from the type series from China by having a larger size (SVL 48.6–51.7 mm in males, SVL 58.4 mm in the females vs. 36.0–40.0 mm in males, 42.0–53.0 mm in females). Genetic distances between the Vietnamese records and the type specimens of O. shiwandashanensis from China varied from 0 to 1.5% (16S gene). Genetic divergences between the Vietnamese records and H. latouchii from the type locality were 2.0–2.6% (16S gene). In addition, morphological data and natural history notes of the aforementioned species are provided, based on the new records from Vietnam.